2023
DOI: 10.2196/41186
|View full text |Cite
|
Sign up to set email alerts
|

Models of Telehealth Service Delivery in Adults With Spinal Cord Injuries: Scoping Review

Shaghayegh Mirbaha,
Ashley Morgan,
Ada Tang
et al.

Abstract: Background In Canada, approximately 86,000 people live with spinal cord injury (SCI), and there are an estimated 3675 new cases of traumatic or nontraumatic etiology per year. Most people with SCI will experience secondary health complications, such as urinary and bowel issues, pain syndrome, pressure ulcers, and psychological disorders, resulting in severe chronic multimorbidity. Moreover, people with SCI may face barriers in accessing health care services, such as primary care physicians’ expert … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“… 62 A recent scoping review concluded that telehealth/telerehabilitation may ensure efficient follow-up, rehabilitative care continuity, early detection of secondary complications, and their management in community-dwelling patients with SCI. 63 An RCT demonstrated that videoconferencing may be used efficiently for the management of pressure injuries in terms of HRQoL, healing, interaction, and satisfaction compared to conventional care for people with SCI. 64 Another RCT pointed to the feasibility, effectiveness, and safety of TeleSCI in terms of improvement in self-care, mobility, and anxiety in individuals with SCI.…”
Section: Resultsmentioning
confidence: 99%
“… 62 A recent scoping review concluded that telehealth/telerehabilitation may ensure efficient follow-up, rehabilitative care continuity, early detection of secondary complications, and their management in community-dwelling patients with SCI. 63 An RCT demonstrated that videoconferencing may be used efficiently for the management of pressure injuries in terms of HRQoL, healing, interaction, and satisfaction compared to conventional care for people with SCI. 64 Another RCT pointed to the feasibility, effectiveness, and safety of TeleSCI in terms of improvement in self-care, mobility, and anxiety in individuals with SCI.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, home-based rehabilitation programs have been limited to using detailed written instructions and illustrations, before evolving into video-based instructions delivered through videotape or digital video disk [57][58][59]61,64,69,72,84]. More recently, the advent of high-speed internet, massive data storage capacity, and affordable digital videography have revolutionized in-home rehabilitation programming, through the emergence of web-based tele-rehabilitation [86][87][88][89]. Specifically, these advancements in telecommunications technology offer a more versatile approach to tele-exercise, which allows clinicians to efficiently create and upload large libraries of custom video content that can be ac-cessed by users from any device with internet connectivity (i.e., tablet, smart phone, etc.).…”
Section: Tele-rehabilitationmentioning
confidence: 99%